International Marketing and Implementation in Business: Case Study in Dominos Pizza - Anwar; Zainal Ruma (PT Maju Malaqbi Makkarana, 2023)
International marketing is the organization of a network of companies to disseminate information about goods and services that meet people's needs globally. International marketing involves companies based in one country selling their products abroad which also has the potential for business expansion. This was also done by one of the American pizza companies, Dominos Pizza, which implemented an international marketing strategy. The purpose of this research is to understand how international marketing affects a company's business expansion process. In this writing, a descriptive qualitative research method with data collection techniques with documentation studies was carried out by the authors. The results obtained from this writing are that by implementing a good and mature international marketing strategy, the company can develop its business globally. Dominos Pizza has successfully proven its existence to date by touching a wider global market share. International marketing begins when a country realizes that they cannot produce goods or services efficiently. Dominos Pizza strives to understand every cultural difference and also consumer demand which certainly has differences in each country that is used as its global business expansion area.